Band Structure Analysis of La0.7Sr0.3MnO3 Perovskite Manganite Using a Synchrotron - Hong-Sub Lee; Hyung-Ho Park (Advances in Condensed Matter Physics)
Oxide semiconductors and their application in next-generation devices have received a great deal of attention due to their various optical, electric, and magnetic properties. For various applications, an understanding of these properties and their mechanisms is also very important. Various characteristics of these oxides originate from the band structure. In this study, we introduce a band structure analysis technique using a soft X-ray energy source to study a La0.7Sr0.3MnO3 (LSMO) oxide semiconductor. The band structure is formed by a valence band, conduction band, band gap, work function, and electron affinity. These can be determined from secondary electron cut-off, valence band spectrum, O 1s core electron, and O K-edge measurements using synchrotron radiation. A detailed analysis of the band structure of the LSMO perovskite manganite oxide semiconductor thin film was established using these techniques.